Analisis Pengaruh Pertumbuhan Ekonomi, Investasi Dan Tingkat Upah Terhadap Kesempatan Kerja Kabupaten/Kota di Provinsi Jambi - Susanto, Ari; Junaidi, Junaidi; Hardiani, Hardiani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2017)
The research entitled â€œAnalyzing The Affect of the Economic Growth, the Investment and the Wage Towards the Employment of regency/city in Jambi Provinceâ€. The purposes of this research were : (1) to analyze the economic growth, the Investments, the wage and the employment regency/city in Jambi province, and (2) to analyze the affect the economic growth, the investment and the wage towards employment regency/city in Jambi Province. With independent variable the economic growth, the Investment and the wage for regency/city while the dependent variable is employment regency/city in Jambi Province. This researcher used panel data regression. The F test indicated that simultaneously the variables of the economic growth, the investments and wage significantly affected employment regency/city in Jambi Province. while t test revealed that partially economic growth and investment affected employment regency/city in Jambi Province positively and significantly, meanwhile the wage insignificant to the employment at the regency/city in Jambi Province.